Intravoxel Incoherent Motion Diffusion-Weighted Imaging for Quantitative Differentiation of Breast Tumors: A Meta-Analysis - Liang, Jianye; Zeng, Sihui; Li, Zhipeng; Kong, Yanan; Meng, Tiebao; Zhou, Chunyan; Chen, Jieting; Wu, YaoPan; He, Ni (Frontiers in Oncology, 2020)
Objectives: The diagnostic performance of intravoxel incoherent motion diffusion–weighted imaging (IVIM-DWI) in the differential diagnosis of breast tumours remains debatable among published studies. Therefore, this meta-analysis aimed to pool relevant evidence regarding the diagnostic performance of IVIM-DWI in the differential diagnosis of breast tumours. Methods: Studies on the differential diagnosis of breast lesions using IVIM-DWI were systemically searched in the PubMed, Embase and Web of Science databases in recent ten years. The standardized mean difference (SMD) and 95% confidence intervals of the apparent diffusion coefficient (ADC), tissue diffusivity (D), pseudodiffusivity (D*), and perfusion fraction (f) were calculated using Review Manager 5.3, and Stata 12.0 was used to pool the sensitivity, specificity, and area under the curve (AUC), as well as assess publication bias and heterogeneity. Fagan’s nomogram was used to predict the posttest probabilities. Results: Sixteen studies comprising 1355 malignant and 362 benign breast lesions were included. Most of these studies showed a low to unclear risk of bias and low concerns regarding applicability. Breast cancer had significant lower ADC (SMD=-1.38, P<0.001) and D values (SMD=-1.50, P<0.001), and higher f value (SMD=0.89, P=0.001) than benign lesions, except D* value (SMD=-0.30, P=0.20). Invasive ductal carcinoma showed lower ADC (SMD=1.34, P=0.01) and D values (SMD=1.04, P=0.001) than ductal carcinoma in situ. D value demonstrated the best diagnostic performance (sensitivity=86%, specificity=86%, AUC=0.91) and highest post-test probability (61%, 48%, 46% and 34% for D, ADC, f and D* values) in the differential diagnosis of breast tumours, followed by ADC (sensitivity=76%, specificity=79%, AUC=0.85), f (sensitivity=80%, specificity=76%, AUC=0.85) and D* values (sensitivity=84%, specificity=5%, AUC=0.71). Conclusion: IVIM-DWI parameters are adequate and superior to the ADC in the differentiation of breast tumours. ADC and D values can further differentiate invasive ductal carcinoma from ductal carcinoma in situ. IVIM-DWI is also superior in identifying lymph node metastasis, histologic grade, and hormone receptors, and HER2 and Ki-67 status.